Fractional-order sinusoidal oscillators: Design procedure and practical examples - Radwan, A.G.; Elwakil, A.S.; Soliman, A.M. (IEEE transactions on circuits and systems. I, Regular papers, 2008)
Sinusoidal oscillators are known to be realized using dynamical systems of second-order or higher. Here we derive the Barhkausen condition for a linear noninteger-order (fractional-order) dynamical system to oscillate. We show that the oscillation condition and oscillation frequency of some famous integer-order sinusoidal oscillators can be obtained as special cases from general equations governing their fractional-order counterparts. Examples including fractional-order Wien oscillators, Colpitts oscillator, phase-shift oscillator and LC tank resonator are given supported by numerical and PSpice simulations.